THE ANALYSIS OF THE BANKRUPTCY LEVEL OF SHARIA INSURANCE COMPANIES IN INDONESIA USING DISCRIMINANT ANALYSIS - Ely Rahmawati; Siti Zulaikha (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the effect of financial performance represented by liquidity ratios, investment and liability ratio, claim expenses, ROA, VOC, and company size on bankruptcy risk. This research was conducted on Islamic insurance companies registered with the Financial Services Authority in the period 2012 to 2018. The statistical model used to test the hypothesis in this study is discriminant analysis at the significance level of 5% (α = 0.05). The results showed that the ratio of investment and liability balances, the ratio of claims expenses, the ratio of return on assets (ROA), volume of capital (VOC) and company size significantly influence the risk of bankruptcy of Islamic insurance companies. However, the dominant financial performance ratios that form the discriminant function in Islamic insurance companies are return on assets, the ratio of claim expenses, and company size.Keywords: Financial Performance, Bankruptcy Risk, Altman Z-Score, Sharia Insurance Company